How Followers Perceive Local Brands: A Case Study of a Food & Beverage Industry’s Instagram Account - Yovan Immanuel; Paramita Widjaya (Journal of Content and Engagement, 2023)
This study analyses a local Surabaya-based cafe and explores its branding through media activity, particularly on Instagram. As Instagram is a widely used social media platform in this day and age, businesses have also tried to expand their reach through said medium. The objective of this research is to find out through this local cafe, whether or not marketing one’s brand (awareness) through Instagram is effective. This is measured through the brand theory and consumer knowledge theory. This research also employs the marketing public relations theory. Data was collected through distributing questionnaires to 110 respondents using purposive random sampling. The questions used in the questionnaire are all based on brand elements as well as factors in consumer knowledge. Based on the researchers’ calculations, the level of knowledge of consumers regarding this local cafe is considered high, thus for this particular cafe, using Instagram as a medium to do marketing communication and increasing brand awareness is considered as effective.